(untitled) (Research, Society and Development, 2024)
The work aims to show a vision of modern industry based on the concept of mass production and its evolution over time. Using a qualitative methodology, we start from the beginnings of the creation of the assembly line by Henry Ford, where he sought to maximize production resources by restricting as much as possible variations in manufacturing processes and items offered, through total quality systems where production processes are more flexible to guarantee the consistency of results. Finally, today’s flexible manufacturing is presented, where customers’ desires and needs reign unchallenged. Information technology through its digital control and supervision systems is presented as an enabling tool for this new industrial revolution. Brazil must make strong advances in this technology to have a world-class industrial park again.